Perspectiva de Análisis Integral de Artefactos Líticos: Casos de Bifaces del sitio Quebrada Seca 3 (Antofagasta de la Sierra, Catamarca) - Hocsman, Salomón (2020)
In this work the parameters and a series of issues on what is called integral perspective in the analysis of lithic artifacts, are exposed. This perspective implies a situated or situational (and conjunctural) study of their life stories through a complementarity of lacking of hierarchy lines which interpellate and dialogue with each other, within a non-destructive or micro-destructive (low impact) approach that is plausible to be implemented in museum materials, in which contextual information is relevant. Then, some bifaces from the Quebrada Seca 3 site (Antofagasta de la Sierra, Catamarca) dating from 5500-4500 years B P, are displayed as selected cases. These artifacts are analyzed from a perspective that integrates multiple complementary and equivalent lines of evidence, namely: detailed techno-typological study, multiple microfossil analysis by polarization microscopy, lipid analysis by Gas Chromatography-Mass Spectrometry (GC-MS), analysis of adhesives used in the hafting through Fourier Transform Infrared Spectrometry (FTIR), and contextual information from the layers considered.